Simultaneous equation 1

Algebra Level 2

{ x y + 2 x + 3 y = 10 1 ( x + 2 ) ( x + 4 ) + 1 ( y + 1 ) ( y + 3 ) = 2 15 \begin{cases} xy +2x +3y = 10 \\ \dfrac 1{(x+2)(x+4)} + \dfrac{1}{(y+1)(y+3)}= \dfrac{2}{15} \end{cases}

Find the number of solutions to the system of equations above.


The answer is 2.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Chew-Seong Cheong
Jan 18, 2020

From x y + 2 x + 3 y = 10 xy+2x+3y = 10 , we have ( x + 3 ) ( y + 2 ) = 16 (x+3)(y+2) = 16 . Let u = x + 3 u=x+3 and v = y + 2 v=y+2 , then u v = 16 uv=16 , and:

1 ( x + 2 ) ( x + 4 ) + 1 ( y + 1 ) ( y + 3 ) = 2 15 1 ( u 1 ) ( u + 1 ) + 1 ( v 1 ) ( v + 1 ) = 2 15 1 2 ( 1 u 1 + 1 v 1 1 u + 1 1 v + 1 ) = 2 15 1 2 ( u + v 2 u v u v + 1 u + v + 2 u v + u + v + 1 ) = 2 15 Since u v = 16 1 2 ( w 2 17 w w + 2 17 + w ) = 2 15 and let w = u + v w 2 34 1 7 2 w 2 = 2 15 w 2 = 64 w = ± 8 2 solutions \begin{aligned} \frac 1{(x+2)(x+4)} + \frac 1{(y+1)(y+3)} & = \frac 2{15} \\ \frac 1{(u-1)(u+1)} + \frac 1{(v-1)(v+1)} & = \frac 2{15} \\ \frac 12 \left(\frac 1{u-1} + \frac 1{v-1} - \frac 1{u+1} - \frac 1{v+1} \right) & = \frac 2{15} \\ \frac 12 \left(\frac {u+v-2}{uv-u-v+1} - \frac {u+v+2}{uv+u+v+1} \right) & = \frac 2{15} & \small \blue{\text{Since }uv=16} \\ \frac 12 \left(\frac {w-2}{17-w} - \frac {w+2}{17+w} \right) & = \frac 2{15} & \small \blue{\text{and let }w=u+v} \\ \frac {w^2-34}{17^2-w^2} & = \frac 2{15} \\ \implies w^2 & = 64 \\ w & = \pm 8 & \small \blue{\text{2 solutions}} \end{aligned}

Therefore, there are 2 \boxed 2 solutions, that is

( u + v ) 2 = 64 u 2 + 2 u v + v 2 = 64 u 2 + 1 6 2 u 2 = 32 u 4 32 u 2 + 256 = 0 ( u 2 16 ) 2 = 0 u = ± 4 v = ± 4 ( x , y ) = ( 1 , 2 ) , ( 7 , 6 ) \begin{aligned} (u+v)^2 & = 64 \\ u^2 + 2uv + v^2 & = 64 \\ u^2 + \frac {16^2}{u^2} & = 32 \\ u^4 - 32u^2 + 256 & = 0 \\ (u^2 - 16)^2 & = 0 \\ \implies u & = \pm 4 \implies v = \pm 4 \\ \implies (x,y) & = (1, 2), (-7, -6) \end{aligned}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...